Synergistic Regulation of S-Vacancy of MoS2-Based Materials for Highly Efficient Electrocatalytic Hydrogen Evolution - Li, Xiao-Yun; Zhu, Shao-Ju; Wang, Yi-Long; Lian, Tian; Yang, Xiao-yu; Ye, Cui-Fang; Li, Yu; Su, Bao-Lian; Chen, Li-Hua (Frontiers in Chemistry, 2022)
Low or excessively high concentration of S-vacancy (CS-vacancy) is disadvantageous for the hydrogen evolution reaction (HER) activity of MoS2-based materials. Additionally, alkaline water electrolysis is most likely to be utilized in industry. Consequently, it is of great importance for fine-tuning CS-vacancy to significantly improve alkaline hydrogen evolution. Herein, we have developed a one-step Ru doping coupled to compositing with CoS2 strategy to precisely regulate CS-vacancy of MoS2-based materials for highly efficient HER. In our strategy, Ru doping favors heterogeneous nucleation and growth of CoS2, which leads to high crystallinity of Ru-doped CoS2 (Ru-CoS2) and rich heterogeneous interfaces between Ru-CoS2 and Ru-doped MoS2-x (Ru-MoS2-x). This facilitates the electron transfer from Ru-CoS2 to Ru-MoS2-x, thereby increasing CS-vacancy of MoS2-based materials. Additionally, the electron injection effect increases gradually with an increase in the mass of Co precursor (mCo), which implies more S2- leaching from MoS2 at higher mCo. Subsequently, CS-vacancy of the as-synthesized samples is precisely regulated by the synergistic engineering of Ru doping and compositing with CoS2. At CS-vacancy = 17.1 %, a balance between intrinsic activity and the number of exposed Mo atoms (EMAs) to boost highly active EMAs should be realized. Therefore, the typical samples demonstrate excellent alkaline HER activity, such as a low overpotential of 170 mV at 100 mA cm-2, and a TOF of 4.29 s-1 at - 0.2 V. Our results promise important application in the fields of electrocatalysis or energy conversion.